Analysis of Organizational Culture and Leadership Style in RST Company - Rosidah, Siti; Gustomo, Aurik (Journal of Business and Management, 2014)
Culture and leadership is one of the important elements in company life, because it can make a significant contribution to the success or failure of an organization. In every company process there is a system that is not visible, but its existence makes the company different from others. The system is the organizational culture that is a characteristic that describes the characteristics of the company, because the organizational culture has a very important meaning that is used as a tool to achieve its goals. Thus with has organizational culture of high quality it will company sustain and compete with the other new companies. This final project is to analyze the organizational culture and leadership style in RST Company. The model used to assess the organizational culture is the Organizational Culture Assessment Instrument (OCAI) by Cameron & Quinn. This model has four cultural types (clan, adhocracy, market, and hierarchy) and of the four cultural has 6 dimensions (dominant characteristic, organizational leadership, management of employee, organizational glue, strategic emphases, and criteria for success). While leadership style using transformational and transactional model and counted with frequency analysis. In collecting the data, the sample used is 33 people by distributing questionnaires. The results of this research is the dominant culture in RST Company are clan, market, and adhocracy culture that emphasizes family clan to be applied in the organization, and leadership style emphasizes transformational that prioritized .Keyword: Organizational culture, leadership style, Organizational Culture Assessment Instrument (OCAI)